ANALISIS PENGARUH TINGKAT PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP TINGKAT PENGANGGURAN DI KABUPATEN MIMIKA - Jeni Palindangan; Abu Bakar (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
This study aims to determine the effect of the rate of economic growth and the human development index on the unemployment rate in Mimika Regency. The research method used in this research is associative research method. The data collection technique used is the documentation technique. To determine the effect of the level of economic growth and the human development index on the unemployment rate in Mimika Regency, Multiple Linear Regression Analysis was used. The results of this study indicate that the level of economic growth has no significant effect on the unemployment rate in Mimika Regency, while the human development index has a significant effect on the unemployment rate.